2003
DOI: 10.1046/j.1365-2486.2003.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vascular plants on carbon turnover and methane emissions from a tundra wetland

Abstract: This paper investigates how vascular plants affect carbon flow and the formation and emission of the greenhouse gas methane (CH4) in an arctic wet tundra ecosystem in NE Greenland. We present a field experiment where we studied, in particular, how species‐specific root exudation patterns affect the availability of acetate, a hypothesized precursor of CH4 formation. We found significantly higher acetate formation rates in the root vicinity of Eriophorum scheuchzeri compared with another dominating sedge in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
288
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(309 citation statements)
references
References 32 publications
10
288
5
Order By: Relevance
“…Also recently fixed substrates may have played a role for high CH 4 emissions from the floating mat. Several studies have found a positive correlation between the rate of photosynthesis and CH 4 emissions (Joabsson and Christensen, 2001;Ström et al, 2003), which has been explained by the quick allocation of assimilated labile carbon to the roots and subsequent exudation to the anaerobic rhizosphere (Dorodnikov et al, 2011). These recent photosynthates serve as a preferential source of CH 4 compared to older more recalcitrant organic matter (Chanton et al, 1995).…”
Section: Spatial Pattern Of Ch 4 and Co 2 Fluxesmentioning
confidence: 99%
“…Also recently fixed substrates may have played a role for high CH 4 emissions from the floating mat. Several studies have found a positive correlation between the rate of photosynthesis and CH 4 emissions (Joabsson and Christensen, 2001;Ström et al, 2003), which has been explained by the quick allocation of assimilated labile carbon to the roots and subsequent exudation to the anaerobic rhizosphere (Dorodnikov et al, 2011). These recent photosynthates serve as a preferential source of CH 4 compared to older more recalcitrant organic matter (Chanton et al, 1995).…”
Section: Spatial Pattern Of Ch 4 and Co 2 Fluxesmentioning
confidence: 99%
“…For example, the photosynthetic activity of trees is correlated strongly with soil respiration in temperate savannah and temperate peatlands (Mikkelä et al 1995;Tang et al 2005; Thomas et al 1996). The release of photosynthates through the rhizosphere provide labile substrate for decomposer organisms (Silvola et al 1996;Ström et al 2003;Wright et al 2011), influencing the diurnal pattern of CO 2 and CH 4 emissions in both temperate and tropical ecosystems (Bahn et al 2009;Wright et al 2013b). Therefore, it is important to measure greenhouse gas fluxes on a diurnal basis, as this allows investigation of biotic and abiotic controls on the temporal variation of greenhouse gas emissions (Armstrong 1971;Ström et al 2003;Wang and Han 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The release of photosynthates through the rhizosphere provide labile substrate for decomposer organisms (Silvola et al 1996;Ström et al 2003;Wright et al 2011), influencing the diurnal pattern of CO 2 and CH 4 emissions in both temperate and tropical ecosystems (Bahn et al 2009;Wright et al 2013b). Therefore, it is important to measure greenhouse gas fluxes on a diurnal basis, as this allows investigation of biotic and abiotic controls on the temporal variation of greenhouse gas emissions (Armstrong 1971;Ström et al 2003;Wang and Han 2005). Importantly, it allows for the separation of long-term drivers which can strongly vary seasonally, e.g., temperature, humidity, and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The preferential colonisation of hummocks or hollows by distinct plant communities reinforces differences due to topography alone by influencing the quantity and quality of soil organic substrate, and altering the aerobic capacity of the peat by transporting O 2 to the rhizosphere. Plants containing aerenchymous tissue can also provide a direct pathway for many GHGs to the atmosphere, bypassing the aerobic peat horizon, and greatly increasing soilatmosphere fluxes (Whiting and Chanton, 1996;Ström et al, 2003;Minkkinen and Laine, 2006). A clear understanding of the major sources of variation within a site is essential both during the set-up of a study, when choosing where to place individual chambers, and during the up-scaling process so that individual chamber fluxes can be correctly weighted in the final estimate.…”
Section: Introductionmentioning
confidence: 99%